Cheating Behavior in EFL Classroom (A Case Study at Elementary School in Sidenreng Rappang Regency) - Asrifan, Andi; Ghofur, Abd.; Azizah, Nur (OKARA: Jurnal Bahasa dan Sastra, 2020)
Cheating is a common problem yet unresolved issue in the classroom. Some factors make the students cheat, and they do it continually. This article aims to find factors that influence student cheating behavior; the strategies used by the English teacher to overcome student cheating behavior; and the difference in student cheating towards gender. This research is a case study using a descriptive qualitative method. The subjects were UPT SDN 1 Rijang Panua, a sample of schools with 4-grade to 6-grade classes. The questionnaire and the interview were used to collect the data. Data analysis techniques were sequential-parts of the study by Starovoytova and Namango. The result shows that: 1) Three categories of factors that influence student cheating behavior namely a) the situational factor; b) the individual factor; and c) the teacher factor; 2) There are four strategies to overcome student cheating behavior in the EFL Classroom such as explaining the bad impact of cheating behavior, instill character education at an early age, give questions-answer or quiz exercises and give appreciation or praise; 3) there is no difference between cheating behavior based on gender